2002
DOI: 10.1128/jvi.76.15.7398-7406.2002
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Human Immunodeficiency Virus Type 1 Gag at Positions L449 and P453 Are Linked to I50V Protease Mutants In Vivo and Cause Reduction of Sensitivity to Amprenavir and Improved Viral Fitness In Vitro

Abstract: Human immunodeficiency virus type 1 (HIV-1) Gag protease cleavage sites (CS) undergo sequence changes during the development of resistance to several protease inhibitors (PIs). We have analyzed the association of sequence variation at the p7/p1 and p1/p6 CS in conjunction with amprenavir (APV)-specific protease mutations following PI combination therapy with APV. Querying a central resistance data repository resulted in the detection of significant associations (P < 0.001) between the presence of APV protease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
158
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(164 citation statements)
references
References 49 publications
4
158
1
Order By: Relevance
“…However, efficient processing at the NC-p2 junction to produce mature NC and p2 is required for FIV infectivity. The processing efficiency of the equivalent HIV-1 NC-p1-p6 cleavage junctions has been extensively examined, and proper temporal cleavage at these sites correlates with viral fitness, replication capacity, and drug resistance (11,40,45,47,49,52). The findings of the current study reinforce the notion that the cleavage and maturation of NC-p2 in FIV and of the equivalent NC-p1-p6 in HIV-1 offer a new potential therapeutic target.…”
Section: Discussionsupporting
confidence: 75%
“…However, efficient processing at the NC-p2 junction to produce mature NC and p2 is required for FIV infectivity. The processing efficiency of the equivalent HIV-1 NC-p1-p6 cleavage junctions has been extensively examined, and proper temporal cleavage at these sites correlates with viral fitness, replication capacity, and drug resistance (11,40,45,47,49,52). The findings of the current study reinforce the notion that the cleavage and maturation of NC-p2 in FIV and of the equivalent NC-p1-p6 in HIV-1 offer a new potential therapeutic target.…”
Section: Discussionsupporting
confidence: 75%
“…Numerous studies supporting the acquisition of fitness-compensatory mutations have been published and recently reviewed by Maisner-Patin and Andersson [1,23]. Among the most clinical relevant reductions in fitness cost associated with antimicrobial resistance include isoniazid-resistant Mycobacterium tuberculosis [33], protease inhibitors-resistant HIV-1 strains [22], azole-resistant Candida albicans [7], and clarythromycin-resistant Helicobacter pylori [4].…”
Section: Discussionmentioning
confidence: 99%
“…In an analysis of a clinical sequence database, the L449F and P453L mutations at the p1/p6 cleavage site in Gag were frequently observed in combination with the major protease inhibitor resistance mutation I50V, although the two cleavage site mutations were not observed together in individual clones derived from patient samples (107). These mutations each partially improved the replication fitness of HIV-1 strains containing the I50V mutation and increased the degree of protease inhibitor resistance; no effect on protease inhibitor resistance was seen when these mutations were introduced into a drug-sensitive laboratory strain (107).…”
Section: Extragenic Interactionsmentioning
confidence: 99%
“…These mutations each partially improved the replication fitness of HIV-1 strains containing the I50V mutation and increased the degree of protease inhibitor resistance; no effect on protease inhibitor resistance was seen when these mutations were introduced into a drug-sensitive laboratory strain (107). In the absence of these mutations, the I50V mutant accumulated uncleaved p1/p6 protein; this abnormality was partially corrected by the addition of one of the cleavage site mutations (107). Those studies also confirmed that purified protease containing the I50V mutation cleaved a mutant p1/p6 cleavage site more efficiently than a wild-type cleavage site (107).…”
Section: Extragenic Interactionsmentioning
confidence: 99%
See 1 more Smart Citation